Management Strategy in Non-Limb-Threatening Acute Ischaemia of Limbs: Should We Rethink? - Syed M. Asim Hussain; Thomas Joseph (Case Reports in Vascular Medicine)
The Society of Vascular Surgery and the International Society of Cardiovascular Surgery identify three types of acute limb ischaemia to inform prognosis and management. Type 1 limb ischaemia is non-limb-threatening and is currently managed conservatively. We describe three cases of Type 1 limb ischaemia with femoropopliteal occlusion that were managed differently. The first case was initially managed conservatively but resulted in an adverse outcome following worsening of ischaemia. Overall, the cases managed with earlier intervention had good outcomes suggesting that conservative management alone may not be sufficient despite resolution of symptoms. The trend in other vessel diseases such as NSTEMI and TIA is towards earlier intervention, for example, PCI and CEA. It is likely that acute limb ischaemia has a similar natural history to these conditions. It is time to consider earlier revascularisation in selected patients with non-limb-threatening ischaemia.